2019
DOI: 10.4103/jfmpc.jfmpc_437_18
|View full text |Cite
|
Sign up to set email alerts
|

A study on the health seeking behavior among caregivers of under-five children in an urban slum of Bhubaneswar, Odisha

Abstract: Background:The under-five children are a vulnerable age group; their mortality reflecting a country's overall development. Timely and appropriate healthcare seeking behavior, if practiced by caregivers, can have a significant impact on survival. The slum dwellers have poor health-seeking behavior due to their lower socioeconomic status, prevailing malnutrition, poor immunization status, overcrowding, poor sanitation, personal and cultural practices, beliefs, and attitude toward healthcare providers.Objectives:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 9 publications
1
18
2
Order By: Relevance
“…The finding agrees with previous studies that reported delay in health-seeking behaviours among diverse populations in Addis Ababa, Ethiopia, Luwero District, Uganda, and Gambella town, Ethiopia (Cherie & Berhanu, 2012;Lubega et al 2015;Tsadik et al, 2019). However, the finding disagrees with previous studies (Begashaw & Tesfaye, 2016;Mishra et al, 2019) that reported good health-seeking behaviours among their respondents. Hence, these factors may constitute barriers to vaccination programmes, including YF and other health services by communities, and may further accentuate poor health-seeking behaviours among the people.…”
Section: Izzisupporting
confidence: 77%
“…The finding agrees with previous studies that reported delay in health-seeking behaviours among diverse populations in Addis Ababa, Ethiopia, Luwero District, Uganda, and Gambella town, Ethiopia (Cherie & Berhanu, 2012;Lubega et al 2015;Tsadik et al, 2019). However, the finding disagrees with previous studies (Begashaw & Tesfaye, 2016;Mishra et al, 2019) that reported good health-seeking behaviours among their respondents. Hence, these factors may constitute barriers to vaccination programmes, including YF and other health services by communities, and may further accentuate poor health-seeking behaviours among the people.…”
Section: Izzisupporting
confidence: 77%
“…A study by Mishra et al on topic "A study on the health seeking behaviour among caregivers of under-five children in an urban slum of Bhubaneswar, Odisha", the place of preference for seeking care was Government Hospital (30.59%) followed by medicine store, private clinics, anganwadi centers and quacks (2.28%). 24 Another study done in Assam by Borah et al reported that Government facilities was preferred by majority (41.8%), followed by health worker (17.5%), family member (16.8%), and private doctor (9.6%) of the participants during any childhood illness. 8,25 With regards to socio-demographic characteristics of caregivers, it has been observed that, percentage of illiteracy for both mother and father were more in rural areas than in urban areas which might be the reason that health seeking behaviour of rural is not better than urban and most of the parents prefer quacks and faith healers as compare to health facility.…”
Section: Discussionmentioning
confidence: 97%
“…Venkatachalam et al (2014) Mishra K et al in their study in an urban slum of Bhubaneswar found that 77.7 % of the under ives had some illness in the preceding 6 months and recorded 213 episodes of different morbidities among 260 children. Mohapatra et al (2019) The place of preference for seeking care was Government Hospital (30.59%) followed by medical store, private clinics, Anganwadi centers and quacks (2.28%). Mohapatra et al (2019) Minz et al in their study in an urban slum of Lucknow, said that the respondents mainly preferred a quali ied private practitioner (65.4%), followed by an unquali ied private practitioner (26.9%) and a tertiary care health center (7.8%).…”
Section: Discussionmentioning
confidence: 99%
“…"The State Of The World's Children" (2019) Factors known to predict increased survival in underives healthcare during an episode of acute illness are mother's age and educational level, family religion and socioeconomic status, seeking health care in time among others. Mohapatra et al (2019) This study is set to look at under ive children's morbidity patterns in a low socioeconomic area of Guntur city by estimating point prevalence, 2 week period prevalence and annual occurrence of illnesses as recalled by the mothers.…”
Section: Introductionmentioning
confidence: 99%